OPTIMALISASI KINERJA TENAGA KEPENDIDIKAN DAN PENDIDIK DALAM PENINGKATAN PELAYANAN DAN KEPUASAAN MAHASISWA PERSPEKTIF AL-QUR’AN) - Rayhaana, Ayna; Shunhaji, Akhmad; Zuhri , Saifudin (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2024)
This article discusses service, both from the academic service aspect, as well as the administrative service aspect of higher education teaching staff with a Qur'anic approach aimed at increasing student satisfaction. This paper uses the method Library Research sourced from the results of studies of various relevant library materials, in the form of books, journals, articles and so on related to the focus of the problem above. In improving administrative services, employees must be professional and apply optimization efforts in providing products and services as guided by the Qur'an. Academic services need to optimize lecturer competencies, namely Pedagogical, Personality, Professional, Social competencies with a Qur'anic approach, then the quality of service will have implications for increasing student satisfaction, it is hoped that this will give rise to loyalty which will provide benefits for universities